Effect of Medically Tailored Meals on Clinical Outcomes in Recently Hospitalized High-Risk Adults. Issue 10 (15th October 2022) - Go, Alan S.; Tan, Thida C.; Horiuchi, Kate M.; Laws, Denise; Ambrosy, Andrew P.; Lee, Keane K.; Maring, Benjamin L.; Joy, Jena; Couch, Cathryn; Hepfer, Paul; Lo, Joan C.; Parikh, Rishi V.; et al.
Abstract : Background: Inability to adhere to nutritional recommendations is common and linked to worse outcomes in patients with nutrition-sensitive conditions. Objectives: The purpose of this study is to evaluate whether medically tailored meals (MTMs) improve outcomes in recently discharged adults with nutrition-sensitive conditions compared with usual care. Research Design: Remote pragmatic randomized trial. Subjects: Adults with heart failure, diabetes, or chronic kidney disease being discharged home between April 27, 2020, and June 9, 2021, from 5 hospitals within an integrated health care delivery system. Measures: Participants were prerandomized to 10 weeks of MTMs (with or without virtual nutritional counseling) compared with usual care. The primary outcome was all-cause hospitalization within 90 days after discharge. Exploratory outcomes included all-cause and cause-specific health care utilization and all-cause death within 90 days after discharge. Results: A total of 1977 participants (MTMs: n=993, with 497 assigned to also receive virtual nutritional counseling; usual care: n=984) were enrolled. Compared with usual care, MTMs did not reduce all-cause hospitalization at 90 days after discharge [adjusted hazard ratio, aHR: 1.02, 95% confidence interval (CI), 0.86–1.21]. In exploratory analyses, MTMs were associated with lower mortality (aHR: 0.65, 95% CI, 0.43–0.98) and fewer hospitalizations for heart failure (aHR: 0.53, 95% CI, 0.33–0.88), but not for any emergency department visits (aHR: 0.95, 95% CI, 0.78–1.15) or diabetes-related hospitalizations (aHR: 0.75, 95% CI, 0.31–1.82). No additional benefit was observed with virtual nutritional counseling. Conclusions: Provision of MTMs after discharge did not reduce risk of all-cause hospitalization in adults with nutrition-sensitive conditions. Additional large-scale randomized controlled trials are needed to definitively determine the impact of MTMs on survival and cause-specific health care utilization in at-risk individuals.